A HER2 Specific Nanobody–Drug Conjugate: Site-Selective Bioconjugation and In Vitro Evaluation in Breast Cancer Models - Anders H. Hansen; Kasper I. H. Andersen; Li Xin; Oliver Krigslund; Niels Behrendt; Lars H. Engelholm; Claus H. Bang-Bertelsen; Sanne Schoffelen; Katrine Qvortrup (Molecules)
A human epidermal growth factor receptor 2 (HER2)-specific nanobody called 2Rs15d, containing a His3LysHis6 segment at the C-terminus, was recombinantly produced. Subsequent site-selective acylation on the C-terminally activated lysine residue allowed installation of the cytotoxin monomethyl auristatin E-functionalized cathepsin B-sensitive payload to provide a highly homogenous nanobody–drug conjugate (NBC), which demonstrated high potency and selectivity for HER2-positive breast cancer models.